The Effect of Land Use and Management on Soil Properties and Processes - Adilson Pacheco de Souza; Frederico Terra de Almeida (Soil Systems, 2025)
As we delve deeper into the complexities of soil properties and processes, we must consider traditional methodologies and innovative approaches that take advantage of advances in soil management and conservation processes [...]